PENINGKATAN PENILAIAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MENERAPKAN MODEL KOOPERATIF TIPE MAKE A MACTH PADA SISWA KELAS VIII SMPN 3 BATI-BATI KECAMATANBATI-BATI KABUPATEN TANAH LAUT - Risna Dewi Arfianti; Muhamad Ramli (Program Studi PAI STAI Al Falah Banjarbaru, 2019)
The purpose of this research is to find out the assessment of the results of the study of Islamic religious education by applying a cooperative model of Make a Match type in students of Grade VIII SMPN 3 Bati-Bati subdistrict of Bati-Bati of Tanah Laut Regency and to know the implementation of a cooperative learning model of Make a MACTH in Islamic religious education. This research is qualitative descriptive research with a type of action class research participant. The subject in this study was all students of grade VIII SMPN 3 Bati-Bati. While the object in this study is improved assessment of learning outcomes and the process of implementing cooperative learning model type Make a Match. Based on the results of the research, it is noted that through the implementation of the type of cooperative learning model of Make a Match can improve the assessment of learning outcomes of Islamic education in grade VIII students SMPN 3 Bati-Bati. This can be known from the successful research indicators that are qualitative indicators and quantitative indicators. The process of applying a cooperative learning model of the Make a Match type in Islamic religious education in grade VIII students SMPN 3 Bati-Bati runs effectively and efficiently according to the steps specified. This is evident from the increasing active students in following the learning process of Islamic religious education. Keywords: enhancement, learning outcomes, Islamic education, learning Model, Make a Match.